Perilaku Ibu dalam Memandikan Bayi Baru Lahir Di Kecamatan Ulumanda Kabupaten Majene - Nurmadinah Syarif; Ashriady Ashriady; Sartika Mansur; Nurliani Nurliani; Nurma Mahfud (FORIKES, 2018)
Bathing baby is an attempt to keep your baby clean, feels fresh, and prevent the possibility of infection (A.Hidayat, 2009). Low Birth Weight babies (LBW) needs serious handling because it is easy to experience the hipotermi that will be the cause of death. Low Birth Weight distributions in Makassar from 3,570 live births there were 286 (8.0%) Low Birth Weight (Health profile of Mamuju Regency, 2013). In baby bathed immediately at birth would result in infants experiencing hypothermia, because the baby's body temperature normal yet when in contact with water will result in the loss of body heat baby because absorbed by water.The purpose of this research was to describe the behavior of the mother in bathing the Newborn in district Ulumanda. The research method used was qualitative in district Ulumanda in September – October 2017. The number of informants 7 persons, composed of a mother who has a baby aged 0 – 28 days and midwife who has lived more than 2 years at the site of the research. The collection of data through in-depth interviews based on observation results against the main informant in bathing the newborn, informant interviews to review to find out the process of mentoring that was given to the mother of the method bathe the baby. The results showed that some still found the mother's behavior that is inappropriate such procedures most informants are not doing hand-washing before bathing baby, do not clean the umbilical cord with wet cotton, not smoothed the tools take a shower after finished showering and not washing hands after bathing the baby. Most of the babies bathed grandmother caused mother has not had the experience of bathing the infant, the mother has been preparing the equipment that will be used during and after bathing the baby. The purpose of bathing the baby according to the mother in Ulumanda associated with the health and hygiene of the baby. The majority of mothers do a massage while bathing the infant in accordance with the directives of the midwife.